If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -60 = -6 Reorder the terms: -60 + 9x = -6 Solving -60 + 9x = -6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 9x = -6 + 60 Combine like terms: -60 + 60 = 0 0 + 9x = -6 + 60 9x = -6 + 60 Combine like terms: -6 + 60 = 54 9x = 54 Divide each side by '9'. x = 6 Simplifying x = 6
| -5y=10x+10 | | 56=17p-26 | | y=1.90+1.40t | | 8v+11=7v-20 | | 6x-14-2x=8x-9 | | 600+0.5(3000+0.05D)=D | | 8x+3-10=2(x-2)+3 | | -1k=287.658 | | 5(x-4)+2=42 | | 0.8b-1.2+2.3=12.2 | | 3.25n=52 | | 8=4sin(5x) | | 9-(4z-8)=1-5z | | 3.25n=53 | | 40-5c=55 | | 9(x-8)=7+8x | | S-2=25 | | 7x-8+2x=2+9x-9 | | 6x-13-3x=5x-6 | | 3.25n=54 | | Ln(9x+11)-Lynx= | | 12x+8=80 | | 12(x+9)=108 | | x^3-343=-0 | | -2(d-3d)=12 | | 6x+66=144 | | 2.2k=6.16 | | 6-(3y-2)=1-4y | | z^2+24z+c=0 | | 3x+y-2z=22 | | 10.6n+15=205.8 | | 6-8x+5x-2= |